2007
DOI: 10.1186/1472-698x-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Chagas disease: an impediment in achieving the Millennium Development Goals in Latin America

Abstract: Background: Achieving sustainable economic and social growth through advances in health is crucial in Latin America within the framework of the United Nations Millennium Development Goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
50
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 19 publications
0
50
0
6
Order By: Relevance
“…Recent research indicates that the sylvatic life cycle of Trypanosoma cruzi was probably well established when humans first peopled the coasts of northern Chile and southern Peru and began acting as parasite hosts (Aufderheide et al, 2004). Today, Chagas remains the most important vector-borne disease in the Americas (Franco-Paredes et al, 2006), although it has also been identified in Europe and North America, due mainly to blood transmission. Vector-borne cases of Chagas disease have been noted in the southern United States (CDC, 2007).…”
mentioning
confidence: 99%
“…Recent research indicates that the sylvatic life cycle of Trypanosoma cruzi was probably well established when humans first peopled the coasts of northern Chile and southern Peru and began acting as parasite hosts (Aufderheide et al, 2004). Today, Chagas remains the most important vector-borne disease in the Americas (Franco-Paredes et al, 2006), although it has also been identified in Europe and North America, due mainly to blood transmission. Vector-borne cases of Chagas disease have been noted in the southern United States (CDC, 2007).…”
mentioning
confidence: 99%
“…Furthermore, not only does primary infection continue to endanger the lives of countless people in the region, but the chronic manifestations of Chagas disease also affect the livelihood of many individuals previously infected. As the trend for global migration increases, the scope of Chagas disease threatens to expand exponentially, from rural to urban areas and endemic to non-endemic regions [3].…”
mentioning
confidence: 99%
“…Atualmente vem sendo reportadas formas alternativas de transmissão desta doença, tais como transfusão de sangue, transplante de órgãos, transmissão vertical (mãe para filho), por ingestão de alimentos ou líquidos contaminados com o T. cruzi ou ainda acidentais, em laboratórios nos quais são manipulados parasitas vivos. (WHO, 2014;CROPTON, 2013;YANO, 2010;FRANCO-PAREDES et al, 2007).…”
Section: Introductionunclassified
“…(WHO, 2015;WHO, 2014;CROPTON, 2013;COURA, BORGES-PEREIRA, 2012;GASCON, BERN, PINAZO, 2010;FRANCO-PAREDES et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation